Association between overweight and characteristics of young adult students: support for nursing care - Jênifa Cavalcante dos Santos Santiago; Thereza Maria Magalhães Moreira; Raquel Sampaio Florêncio (Universidade de São Paulo, 2015)
OBJECTIVE: to verify associations between overweight and the characteristics of young adult students to support nursing care. METHOD: case-control study conducted with young adults from public schools. The sample was composed of 441 participants (147 cases and 294 controls, with and without excess weight, respectively). Sociodemographic and clinical characteristics were collected together with exposure factors and anthropometrics. Multiple logistic regression was used. The study received Institutional Review Board approval. RESULTS: statistically significant association with overweight: non-Caucasian, having a partner; weight gain during adolescence, mother's excess weight, the use of obesogenic medication, augmented diastolic blood pressure, of abdominal circumference and waist/hip ratio. In addition to these, schooling and weight gain during childhood were also included in the multivariate analysis. After adjustment, the final model included: having a partner, weight gain during adolescence, augmented diastolic blood pressure and abdominal circumference. CONCLUSION: the analysis of predictor variables for excess weight among young adult students supports nurses in planning and developing educational practices aimed to prevent this clinical condition, which is a risk factor for other chronic comorbidities, such as cardiovascular diseases.